(untitled) (Neo Science Peer Reviewed Journal, 2023)
This article analyzes the structural features of the vehicles that affect the vehicle’s technical condition and traffic safety. Recommendations have been developed to reduce the occurrence and impact of road accidents due to the deterioration of the technical condition of vehicles.